2015
DOI: 10.1214/14-ba889
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Structure Learning in Sparse Gaussian Graphical Models

Abstract: Decoding complex relationships among large numbers of variables with relatively few observations is one of the crucial issues in science. One approach to this problem is Gaussian graphical modeling, which describes conditional independence of variables through the presence or absence of edges in the underly- ing graph. In this paper, we introduce a novel and efficient Bayesian framework for Gaussian graphical model determination which is a trans-dimensional Markov Chain Monte Carlo (MCMC) approach based on a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
193
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(197 citation statements)
references
References 45 publications
0
193
1
3
Order By: Relevance
“…Bayesian interpretation had already appeared in the original paper introducing lasso [26], for a detailed Bayesian interpretation, see comments from C. Holmes in [27]. Furthermore, full-fledged Bayesian Lasso and Bayesian graphical lasso were also reported in [14], [15], [28]. However, scalable, full Bayesian extension of graphical lasso for discrete data, especially with options for including higherorder interactions is currently not available.…”
Section: A Graphical Lasso Based Approachesmentioning
confidence: 99%
“…Bayesian interpretation had already appeared in the original paper introducing lasso [26], for a detailed Bayesian interpretation, see comments from C. Holmes in [27]. Furthermore, full-fledged Bayesian Lasso and Bayesian graphical lasso were also reported in [14], [15], [28]. However, scalable, full Bayesian extension of graphical lasso for discrete data, especially with options for including higherorder interactions is currently not available.…”
Section: A Graphical Lasso Based Approachesmentioning
confidence: 99%
“…16,17 Parametrik model alternatifleri içinde ise en öne çıkanları Kopula GGM modelidir. 18,19 Bu model, kısaca, GGM ifadesindeki çok değişkenli normal dağılım fonksiyonunun, Gaussian kopula yardı-mıyla yazılmasından türetilmiştir. Diğer yandan verinin özellikle zaman bağlı olması durumunda durum uzay modelleri ve zaman serisi GGM ifadeleri geliştirilmiştir.…”
Section: İleri̇ Modellerunclassified
“…Bahsedilen modellerin tahmininde optimizasyona dayalı yöntemlerin yanı sıra, cezalandırılmış olabilirlik, ters atlamalı markov zinciri Monte Carlo ve doğum-ve-ölüm algoritması gibi parametrik tahmin yöntemleri ve eşik meyil iniş algoritması gibi parametrik olmayan yöntemler sıklıkla kullanılmaktadır. 10,18,19,22 Fakat modelleme ve parametre tahmin yöntemleri halen bu konudaki araştırma başlıklarıdır. Bu nedenle her geçen gün yeni ifadelerin tanımlanması ve uygun algoritmaların geliştiril-mesi konularında, çalışmalar yapılmaya devam edilmektedir.…”
Section: İleri̇ Modellerunclassified
“…In the study of Dobra and Len [3], this method is used to infer the parameters of the copula Gaussian graphical model (CGGM). In the application of CGGM for the construction of biological networks, it is found that RJMCMC has a long burn-in period [3,4] and additionally, it needs to calculate the Jacobian term for each associated iteration, as in Eq. (2).…”
Section: Introductionmentioning
confidence: 99%
“…In order to decrease the computational demand and optimize the calculation, Mohammadi and Wit [4] suggest the birth-and-death method. RJMCM with the splitmerge approach have been also intensively studied in the work of Richardson and Green [5].…”
Section: Introductionmentioning
confidence: 99%